2015
DOI: 10.1371/journal.pone.0138309
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Pattern, Processing Factors, and Safety Evaluation for Dimethoate and Its Metabolite (Omethoate) in Tea (Camellia Sinensis)

Abstract: Residue levels of dimethoate and its oxon metabolite (omethoate) during tea planting, manufacturing, and brewing were investigated using a modified QuEChERS sample preparation and gas chromatography. Dissipation of dimethoate and its metabolite in tea plantation followed the first-order kinetic with a half-life of 1.08–1.27 d. Tea manufacturing has positive effects on dimethoate dissipation. Processing factors of dimethoate are in the range of 2.11–2.41 and 1.41–1.70 during green tea and black tea manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
0
20
3
Order By: Relevance
“…Pesticides residues in tea can be transferred into tea infusion and then consumed by humans [310]. As previously noted, it has also been found that coexposure to F and aluminium or pesticides, such as CPF, results in synergistic interactions and enhanced toxicity [275280].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Pesticides residues in tea can be transferred into tea infusion and then consumed by humans [310]. As previously noted, it has also been found that coexposure to F and aluminium or pesticides, such as CPF, results in synergistic interactions and enhanced toxicity [275280].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Dissipation rates also have application in consumer safety. For example, these values are used in calculations for predicting residue concentrations in harvested produce and for determining the time interval needed between crop spraying and harvesting or potential processing/consumption in order to minimise residue concentrations [4,5]. Dissipation rates also have value when considering the potential risk to non-target and beneficial organisms (e.g., pollinators) that may forage or otherwise come in contact with a pesticide treated plant, as well as informing on how long the chemical is likely to offer satisfactory pest control before it decays [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Evaporation, rain-rinse, photolysis, hydrolysis, metabolism and growth dilution are important degradation processes influencing the fate of pesticides in or on plants. [9][10][11][12] Evaporation, rain-rinse and photolysis mainly occur on the leaf surface. [13][14][15][16] Some AIs can be taken up by the leaf, where they would be subjected to different environmental variables.…”
Section: Introductionmentioning
confidence: 99%